Sales and Purchase Accounting Information Systems In Trading Companies - Devina Gunadi; Bernardinus Harnadi; G. Freddy Koeswoyo (Soegijapranata Catholic University, 2022)
Effective and efficient record of sales and purchase transactions are increasingly needed, especially in large transactions. This research is conducted at the “Toko Beras Dadar” in Peterongan Market. This shop still uses manual records. The difficult for manual record is to keep track of the existing stock of goods. This shop has not compiled trial balance and income statement according to standard. So, this problem must be solved with a website-based sales accounting information system. The program used are Laravel and MySQL. The results of technical testing show the system can run well and help the user to simplify transaction process.